Speech Recognition in Noise by Younger and Older Adults: Effects of Age, Hearing Loss, and Temporal Resolution. (April 2016) - Vermeire, Katrien; Knoop, Allart; Boel, Carolien; Auwers, Silke; Schenus, Laura; Talaveron-Rodriguez, Marilina; De Boom, Chloë; De Sloovere, Marleen
Objectives: Purpose of the present study is to evaluate the effects of aging on temporal resolution and speech understanding in noise. Methods: Twenty-seven young and 33 older normal hearing adults participated in this study. Temporal resolution was investigated using the Gaps in Noise (GIN) test. Understanding sentences in noise was investigated using a Dutch sentences (LIST) test. Results: Results demonstrated that older adults have significantly worse temporal resolution scores and significantly greater difficulty understanding sentences in noise than younger adults. In the group of older adults, the ability to understand sentences in noise correlated with hearing and age. A stepwise regression analysis showed that age was the best predictor for the speech in noise results. However, temporal resolution correlated with hearing, not with age. Results from the GIN test did not correlate with the results from the LIST test. Conclusions: The present study shows that with advancing age, both temporal resolution and speech understanding in noise significantly diminish. Temporal resolution correlates with hearing, not age, while speech understanding correlates more with age than hearing. These results could have implications for the outcome of auditory prostheses in older adults, as both diminished temporal resolution and speech understanding have to be taken into account.